Friday

August 1, 2014

August 1, 2014

Posted by **olivia** on Friday, March 23, 2012 at 6:01pm.

- precal -
**Ron**, Friday, March 23, 2012 at 6:19pmcotx=cosx/sinx

Therefore, (cosx/sinx)sinx=cosx

cosx=cosx

**Related Questions**

Precal - Verify the identity: sin^(1/2)x*cosx - sin^(5/2)*cosx = cos^3x sq root ...

precal - 1-cosx/1+cosx=(cotx-cscx)^2

precal - 1/tanx-secx+ 1/tanx+secx=-2tanx so this is what I did: =tanx+secx+tanx-...

precal - 4(sinx)(cosx)+2(sinx)-2(cosx)-1=0 Find x in radians I can't figure this...

precal - fixed typo ((sinx + cosx)/(1 + tanx))^2 + ((sinx - cosx)/(1 - cotx))^2...

Pre-Calc - Trigonometric Identities Prove: (tanx + secx -1)/(tanx - secx + 1)= ...

Math - Verify the identity . (cscX-cotX)^2=1-cosX/1+cosX _______ sorry i cant ...

Trigonometry Check - Simplify #3: [cosx-sin(90-x)sinx]/[cosx-cos(180-x)tanx] = [...

precal - please help i can't find the answer for this question. i can only ...

precal - cosx/sinxcotx=1